Heart Rate Turbulence and T‐Wave Alternans in Patients with Coronary Artery Disease: The Influence of Diabetes. Issue 5 (15th January 2015) - Perkiömäki, Juha; Exner, Derek V.; Piira, Olli‐Pekka; Kavanagh, Katherine; Lepojärvi, Samuli; Talajic, Mario; Karvonen, Jarkko; Philippon, Francois; Junttila, Juhani; Coutu, Benoit; Huikuri, Heikki
<x xml:space="preserve">Abstract</x> Background Patients with diabetes mellitus (DM) have a higher risk of sudden cardiac death. Factors associated with the risk profiles of coronary artery disease (CAD) patients with DM are not well established. Heart rate turbulence (HRT) and T‐wave alternans (TWA) are often used to predict arrhythmia events. Methods and Results HRT and TWA were measured in two independent groups: the ARTEMIS cohort study and the REFINE‐ICD randomized trial. ARTEMIS assesses risk 3–12 months after coronary angiography in patients with CAD. The initial 1001 patients in ARTEMIS, 526 with and 475 without DM, are included in this analysis. REFINE‐ICD compares usual care versus usual care plus ICD therapy in patients with left ventricular (LV) ejection fraction (EF) values of 36–50% assessed 2–15 months after myocardial infarction. The initial 275 patients screened in REFINE ICD are included in this analysis. Abnormal HRT plus TWA was more common in patients with versus without DM in ARTEMIS (125/526, 24% vs 63/475, 13%; P < 0.001) and REFINE‐ICD (43/55, 78% vs 55/220, 25%; P < 0.001), respectively. Abnormal HRT plus TWA was also more common in patients with LVEF values < 50% (28%) vs ≥ 50% (18%; P < 0.001) in ARTEMIS and LVEF values below the population median of 42% (60/138, 43%) versus above the median (38/137, 28%; P < 0.01) in REFINE‐ICD. Conclusions Abnormal HRT plus TWA is more common in CAD patients with DM compared with the patients without DM and is related to the severity of LV dysfunction. Clinical Trial Registration Information http://www.clinicaltrials.gov, NCT01426685; http://www.clinicaltrials.gov, NCT00673842.